निमाड़ी संस्कृति और साहित्य - Nirgune, Vasant (Aadivasi Lok Kala evm Boli Vikas Academy Madhya Pradesh Sanskriti Parishad, 2002)
This book emphasizes on the various aspects and importance of Nimadi culture and literature.
Nimadi Sanskriti aur Sahitya
Keywords: निमाड़ी संस्कृति और साहित्य; Nimadi Sanskriti aur Sahitya; Folk Culture; Hindi; Hindi; Nimadi